Frozen embryo transfer or fresh embryo transfer: Clinical outcomes depend on the number of oocytes retrieved. (August 2017) - Xu, Bing; He, Ya-qiong; Wang, Yuan; Lu, Yao; Hong, Yan; Wang, Yao; Sun, Yun
Abstract: Objective: To establish a safe and effective clinical transplantation strategy for determining when to prioritize frozen embryo transfers (FET) or fresh embryo transfers (ET) we conducted a retrospective analysis study, examining several key clinical outcomes. Study design: In a retrospective cohort study, 1423 patients (age < 40) were categorized into four groups according to the number of oocytes retrieved (15–18, 19–21, 22–24 and ≥25 oocytes). The clinical outcomes of 1423 in vitro fertilization (IVF) cycles (896 fresh ET and 527 FET) were reviewed for each group. Data demonstrated that the clinical pregnancy rates (PR) and live birth rate (LBR) of the FET group was higher than those of the fresh ET group. Results: Our study further indicates that the clinical benefits of FET become most meaningful when the number of oocytes retrieved ≥19. When the number of oocytes retrieved ≥20, this difference was more significant, with benefits in PR(odds ratio [OR] = 2.46, 95% confidence interval [CI]: 1.74-3.46, P < 0.001) and LBR (OR = 2.27, 95% CI: 1.60–3.22, P < 0.001). Conclusion: 20 oocytes retrieved may be the optimal cut-off point number for FET in order to achieve both a successful pregnancy and a live birth.